Population Attributable Risk (PAR) of Hyperuricemia for Diabetes Mellitus in 20-74-Year-Old Population of Yazd during a 10-Year Longitudinal Cohort: Yazd Healthy Heart Cohort (YHHC) in Iran - Ahmad Karimi; Seyedeh Mahdieh Namayandeh; Hosein Fallahzadeh; Masoud Rahmanian; seyed Mahmoud Sadr-Bafghi; Mohammadhosein Soltani; Leila Hadiani; Samaneh Jalilian; Mohammad-Taghi S; Mojtaba Mohammadhoseini; Fatemeh Majidpour; Maryam Askari (Shahid Sadoughi University of Medical Sciences, 2018)
Introduction: Taking into consideration the high impact of Diabetes Mellitus type II (DM II) on human's health, identification of risk factors to prevent its development seems essential. Further studies are needed to ensure the positive role of uric acid in the onset of diabetes. This study targeted at investigating the attributed risk of hyperuricemia for the onset of DM II. Methods: In the present study, 1641 non-diabetic people, selected through multi-stage random cluster sampling, were followed up for 10 years (2006 - 2016). During the study, data on the variables of the study were collected and entered in SPSS 16 which was used to analyze the data. To calculate the attributions of hyperuricemia in the risk of developing diabetes, Levin's formulas and attributable risk related to the prevalence of exposure during these ten years were used. Results: Findings showed that 54.8% of people with hyperuricemia suffered from DM II., whereas 28.2% of people with normal uric acid level developed diabetes. The Attributable Risk (AR) of hyperuricemia and 75th percentile of serum uric acid for DM II were calculated by the weighted attributable risk formula which was 3.6 % and 24.2 %, respectively. With the treatment of high uric acid, the probability of the incidence of diabetes in hyperuricemia patients was reduced to 24.2% over a 10-year period. Conclusion: In this study, there was a significant correlation between high uric acid level and the risk of diabetes. Therefore, necessary measurements should be taken to treat the hyperuricemia patients in order to prevent the incidence of diabetes caused by high blood acid uric.